A Case for Better Articulating the Value of Expanding Higher Education - Stern, Vivienne; Castell, Ed (International Higher Education, 2024)
Across the world, more people are being educated to a higher level. Yet, in some mass higher education systems—including the United Kingdom—criticisms are being leveled at the expansion of higher education. To advocate for continued expansion, we must deepen our own and decision-makers’ understanding of the breadth of benefit to the individual, to the wider economy, and to equity of opportunity